KEANEKARAGAMAN JENIS ANGGREK DI KAWASAN TAMAN NASIONAL LORE INDU ( Studi Kasus Desa Mataue, Kecamatan Kulawi, Kabupaten Sigi Provinsi Sulawesi Tengah) - Pemba, Stevi; Mallombasang, Sri Ningsih; Muslimin, Muslimin (Universitas Tadulako, 2015)
Orchids known from orchidaceae is the largest family of flower in number though facing increace in theats particularly its natural habitat. Therefore, baseline study regarding its species diversity is important to carry out specially in village surround the Lore Lindu National Park such as in Mataue Village. The main objective of this study was to identify species and its diversity. Four line transects with each 200 hundreds meters in length end each with five plots with 20 m x 20 m in size were applied. The distance between plot was 20 m and there were 20 plots altogether. The result of the study found that there were 21 species indentified in the research location Aerides odorata, Agrostophyllum majus.J.J Sm., Bulbophyllum SPL., Bulbophyllum lobbi Lindl, Calanthe sp, Coelogyne asperata Lindl, Coelogyne foerstermannii Rchb. F.,Cymbidium ensifolyum L.SW., Cyimbidium lancifolium Hook., Cymbidium pinalaysonianum, Dendrobium crumenatum sw, Dendrobium macrosphyllum, Dendrochyllum sp, Eria sp, Grammatophyllum scriptum.Bl, Grammatophyllum stepeliiflorum J.J.S., Liparis lacerata, Podochillus macrophyllus Lind, Spathoglottis plicata BI, vanda sp, vanda arculata. From the important Value Index, cymbidium ensifolyum L.SW was found to dominate the entire orchids. Overall, diversity index (H’) estimated to be about 2.164. Keywords: orchids, Mataue Village, Lore Lindu National park.